2004
DOI: 10.1016/j.neuron.2004.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Waves Propagate through Radial Glial Cells and Modulate Proliferation in the Developing Neocortex

Abstract: The majority of neurons in the adult neocortex are produced embryonically during a brief but intense period of neuronal proliferation. The radial glial cell, a transient embryonic cell type known for its crucial role in neuronal migration, has recently been shown to function as a neuronal progenitor cell and appears to produce most cortical pyramidal neurons. Radial glial cell modulation could thus affect neuron production, neuronal migration, and overall cortical architecture; however, signaling mechanisms am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
492
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(538 citation statements)
references
References 63 publications
(7 reference statements)
27
492
2
5
Order By: Relevance
“…For example, radial glial cells serve several functions during development, including migration of neurons and astrocytes and functioning as a progenitor cell pool for astrocytes (Goldman, 2003). Kriegstein and colleagues (Weissman et al, 2004) have demonstrated that radial glial cell migration and differentiation are regulated through purinergic signaling mediated by P 2 Y receptors. Progenitor cell proliferation from neurospheres can be regulated in an autocrine manner by pulsatile release of ATP from the progenitor cells themselves that decreases over several days in vitro (Lin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For example, radial glial cells serve several functions during development, including migration of neurons and astrocytes and functioning as a progenitor cell pool for astrocytes (Goldman, 2003). Kriegstein and colleagues (Weissman et al, 2004) have demonstrated that radial glial cell migration and differentiation are regulated through purinergic signaling mediated by P 2 Y receptors. Progenitor cell proliferation from neurospheres can be regulated in an autocrine manner by pulsatile release of ATP from the progenitor cells themselves that decreases over several days in vitro (Lin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During mitosis, several studies have illustrated that RG cells remain in place without retraction from the pial surface throughout the whole cell cycle (Miyata et al, 2001;Noctor et al, 2001Noctor et al, , 2002Tamamaki et al, 2001;Weissman et al, 2004). Within the radial fiber of RG cells, the cytoplasm climbs toward the cell body with varicosities showing at intervals along the attenuated fiber (Miyata et al, 2001;Noctor et al, 2001Noctor et al, , 2002Tamamaki et al, 2001;Weissman et al, 2004).…”
Section: Rg Cell Division In Neocortical Developmentmentioning
confidence: 99%
“…They also show that during the transition from the symmetric to asymmetric (neurogenic) divisions-when the G1 phase lengthens (Caviness et al, 1995;Takahashi et al, 1995)-the Ca waves dynamics significantly changes (see Fig. 7B in Weissman et al, 2004). These data lead to the postulation that Ca waves dynamically modulate the cell cycle within clusters of neighboring NEcs providing a temporal and spatial framework for an organized Each binary signal was divided into cph and cd halves.…”
Section: The Search Formentioning
confidence: 86%
“…Additionally, it has been reported that waves of intracellular Ca transients spontaneously appear and propagate through restricted spatial domains occupied by proliferating NEcs (Owens and Kriegstein, 1998;Noctor et al, 2004). Weissman et al (2004) have demonstrated that, in the developing rat neocortex, Ca waves are initiated by individuals NEc in late G1 or S phase by means of connexin hemichannels opening and ATP release; ATP acts on neighboring NEcs by activating the P2Y1 ATP receptor which, in turn, activates the IP3 signaling pathway leading to the production of Ca transients in adjacent NEcs. They show that Ca waves display a pattern of temporal clusters and that nearby waves often occur sequentially, in clusters radiating both spatially and temporally from one origin.…”
Section: The Search Formentioning
confidence: 99%
See 1 more Smart Citation